2019
DOI: 10.1111/labr.12170
|View full text |Cite
|
Sign up to set email alerts
|

Who Buffers Income Losses after Job Displacement? The Role of Alternative Income Sources, the Family, and the State

Abstract: Using survey data from the German Socio‐Economic Panel (SOEP), this paper analyses the extent to which alternative income sources, reactions within the household context, and redistribution by the state attenuate earnings losses after job displacement. Applying propensity score matching and fixed effects estimations, we find that income from self‐employment reduces the earnings gap only slightly and severance payments buffer losses in the short run. On the household level, we find little evidence for an added … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 49 publications
3
9
0
Order By: Relevance
“…The findings of the study concur with those of Rithaa and Mugambi [7] and Agesa et al [20] who reported that farmers who had access to extension services had improved management skills of their farms. Furthermore, the study's findings agreed with Suhartono and Widiyanto [13] and Fackler and Weigt [21] who reported that agricultural research was transformative and helped farmers achieve sustainable income among farmers. The extension services are vital in the dissemination of information through practices such as plant clinics.…”
Section: Mean Importance In a Scale Of 1-5 Of Extension Research Ansupporting
confidence: 83%
See 1 more Smart Citation
“…The findings of the study concur with those of Rithaa and Mugambi [7] and Agesa et al [20] who reported that farmers who had access to extension services had improved management skills of their farms. Furthermore, the study's findings agreed with Suhartono and Widiyanto [13] and Fackler and Weigt [21] who reported that agricultural research was transformative and helped farmers achieve sustainable income among farmers. The extension services are vital in the dissemination of information through practices such as plant clinics.…”
Section: Mean Importance In a Scale Of 1-5 Of Extension Research Ansupporting
confidence: 83%
“…The low education level in Chuka Sub-County is one factor that reduces access to research findings as most of the information is presented in online or printed platforms. On the contrary, Fackler and Weigt [21] stated that most farmers had developed on-farm research that they conduct in groups to establish which varieties perform well in their region.…”
Section: Institutional Factors Affecting Optimization Of Coffee Produmentioning
confidence: 99%
“…argues that, in the case of job loss, the household is the primary source of buffer against earnings losses for couples, although much more so in the US than in Germany. Others emphasize that social security, specifically unemployment insurance in the first years and minimum income schemes in the following years, are the primary source of compensation in the case of job loss, where the level of replacement of household income ranges between 10-25% in the UK and the US, 35-50% in Canada and Switzerland, and 65-70% in Germany and Norway (Hardoy and Schone, 2014;Fackler and Weigt, 2020;Stepner, 2019;Di Nallo and Oesch, 2021).…”
Section: Existing Evidencementioning
confidence: 99%
“…For Germany, there are several studies analysing the added worker effect based on SOEP data. Despite őnding substantial and persistent earnings losses of displaced workers, Fackler and Weigt (2020) őnd no evidence for a signiőcant added worker effect when analysing partners' earnings after displacement. Triebe (2015) provides evidence for an added worker effect for married but not for unmarried couples.…”
Section: Introductionmentioning
confidence: 96%
“…The absence of a meaningful added worker effect for Germany is often explained by the generous tax and transfer system mitigating the income shock resulting from unemployment to such a large extent that partners' incentives to increase working hours are low (e.g. Ehlert, 2012;Fackler and Weigt, 2020). However, the vast majority of existing studies focus on the partner's realised labor supply responses and interpret these as fully reŕecting labor supply preferences.…”
Section: Introductionmentioning
confidence: 99%